Watermarking in protecting and validating the integrity of digital information: a case study of the holy scripture - Olanrewaju, Rashidah Funke; Fajingbesi, Fawwaz Eniola; Ishak, Nur Azimah (The Institute of Electrical and Electronics Engineers, Inc., 2016)
This paper presents digital watermarking for validating and protecting the integrity of digital Holy Quran in Portable Document Format (PDF). The need arises as minute alteration to text or content of Holy Scriptures could result in a devastating situation in the belief of the owners. By this research we have designed and evaluated a simple yet fragile and fidel image PDF digital watermarking technique using 2 and 4 level Discrete Wavelet Transform (DWT) in order to protect and detect the authenticity of a digital Holy Quran. A 512×512 PDF Quran was used as cover image and DWT carried out on it following the watermark image embedding process of a 128×128 and 32×32 on different trials. The Inverse DWT then carried out to obtain the watermarked Quran PDF. Imperceptibility test using Peak Signal to Noise Ratio (PSNR) and Structural Similarity Index (SSIM) were used to evaluate the fidelity and fragility of the watermark scheme over four different embedding gain (k) of 0.001, 0.002, 0.003 and 0.004 for a more robust system. The experimental results demonstrated that our system was indeed effective.